Backmatter (Author Guideline, Publication Ethics, Copyright Transfer Agreement for Publishing Form) (Bulletin of Chemical Reaction Engineering & Catalysis, 2013)
Backmatter (Author Guideline, Publication Ethics, Copyright Transfer Agreement for Publishing Form)